Energy and hygrothermal performance of cross laminated timber single-family homes subjected to constant and variable electric rates. (September 2019) - Setter, Lewis; Smoorenburg, Eric; Wijesuriya, Sajith; Tabares-Velasco, Paulo Cesar
Abstract: Cross Laminated Timber (CLT) is a panelized mass timber product suitable for sustainable building construction that can reduce building energy use and cooling electricity peak demand. Previous studies have shown that CLT has a market in the US for tall commercial buildings. However, most of the current CLT literature has not consider application in residential construction. Residential building energy use is highly susceptible to weather. Thus, it has the potential to benefit from using CLT as the envelope material given its natural massiveness and enhanced air-tightness. Furthermore, the construction advantages of CLT make it a candidate for rapidly growing residential areas. This study numerically analyzes potential energy savings when CLT is implemented in a single-family home in different US climates. A typical new wood frame home is compared against the same house implemented with CLT construction. The effects of increased thermal mass and reduced infiltration are taken into account in order to determine the impact of CLT on the energy consumption. This study also considers the use of variable thermostat setpoints to introduce precooling strategies with the objective of reducing cooling electricity energy cost when time-of-use (TOU) electricity rates are available. In addition, this study examines temperature and humidity changes in CLT homes using WUFI software, a wall assembly simulator used to analyze thermal and moisture transfer. The thermal changes throughout the wall assemblies indicate the enhanced sensible storage capabilities, insulation performance of CLT, as well as ensure that the CLT assembly is physically practical, with no significant moisture accumulation that can lead to rot or mold. Highlights: Analysis includes CLT with different cooling setpoints and 3 locations in the U.S. Combine energy and hygrothermal simulations for CLT residential building. Maximum heating cost savings up to 36% for Boston. Maximum cooling cost savings up to 17% for Phoenix.